Autism Spectrum Disorder, Oral Implications, and Oral Microbiota - Emiliana D’Angelo; Fausto Fiori; Giuseppe A. Ferraro; Assunta Tessitore; Luca Nazzaro; Rosario Serpico; Maria Contaldo (Children)
Background/Objectives: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by difficulties in social interaction, communication, and repetitive behaviors. Recent evidence indicates a significant relationship between ASD and imbalances in microbiota, particularly in the oral and gastrointestinal areas. This review examines the impact of oral microbiota, self-injurious behaviors (SIB), sensory sensitivity, and dietary choices on the comorbidities associated with ASD. Methods: An extensive literature review was conducted using PubMed and Scopus. The focus was on human studies with full-text availability, utilizing search terms related to ASD, oral health, oral microbiota, and neurodevelopmental disorders. The research was evaluated for methodological quality and its relevance to the connections between microbiota, oral health, and ASD. Results: Individuals with ASD face unique oral health challenges, including injuries from self-injurious behaviors and increased sensory sensitivity, which complicate oral hygiene and care. Selective eating can lead to nutritional deficiencies and worsen oral health issues. Dysbiosis in oral and gut microbiota, marked by altered levels of acetate, propionate, and butyrate, interferes with gut-brain and oral-brain connections, contributing to behavioral and neurological symptoms. Treatment options such as probiotics, fecal microbiota transfer, and sensory integration therapies can potentially alleviate symptoms and improve quality of life. Conclusions: The relationship between ASD, oral health, and microbiota suggests a bidirectional influence through neuroinflammatory mechanisms and metabolic disturbances. Proactive strategies focusing on microbiota and dental health may help reduce comorbidities and enhance the overall management of ASD, underscoring the need for further research into microbiota–host interactions and their therapeutic potential.